Differences in newborn umbilical cord care - Sanja Kanisek; Nada Prlić; Ivana Barać; Lorna Dubac Nemet (Medicinski glasnik, 2015)
Aim: To investigate the frequency of different cord care practices as well recommendations to parents on cord care, along with the need to identify as well as reach the consensus on best cord care practices and other procedures in newborn care among health workers. Methods: The study was conducted among 110 health care workers at the nursery departments in two general hospitals, six community-health nursing services and 16 pediatric practices in Eastern Croatia. The questionnaire created for this research has evaluated different cord care practices and recommendations to parents, a need to identify, as well as reach the consensus on best practices in cord care and other procedures in newborn care. Results: Statistically significant differences have been found among respondent groups in three “dry“ cord practices (p=0.000, p=0.002, and p=0.004, respectively) and three “wet“ cord practices (p=0.000, p=0.001, and p=0.000, respectively). Significant differences were determined in three types of recommendations to parents about the care of ”dry” cord (p=0.000, p=0.000, and p=0.002, respectively) and two recommendations for ”wet” cord (p =0.000, p=0.000, respectively). The majority of respondents stressed the need for publishing guidelines on cord care, 104 (94.5%), and for other procedures in newborn care, 108 (98.2%). More than a half of respondents, 63 (57.3%), declared the need to reach a national agreement on guidelines for umbilical cord care. Conclusion: Healthcare workers employ, as well as recommend, different umbilical cord care practices. It is necessary to prepare and reach a national agreement on written guidelines for umbilical cord care as well as for other procedures in newborn care.
Keywords: guidelines; health care workers